2004
DOI: 10.1348/096317904774202126
|View full text |Cite
|
Sign up to set email alerts
|

Employee stock ownership plans and three‐component commitment

Abstract: Previous studies of employee ownership have conceptualized its chief attitudinal outcome principally as an emotional bond to the organization (i.e. affective commitment), despite a growing consensus that commitment is multifaceted. Using a sample of airline pilots, we assessed relationships between ESOP (employee stock ownership plan) attributes and three‐component commitment (Meyer & Allen, 1991). Regarding continuance commitment, high financial value was associated with pilots feeling freer to leave rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
(96 reference statements)
1
25
0
5
Order By: Relevance
“…The literature has found that role clarity has an important role in employees' commitment towards their organizations (Bożena Bednarek-Michalska, 2002;Chi Ming Chow & Brian H. Kleiner, 2002;Manning et al, 2012;Parasuraman et al, 1990;Probst, 2003;Saks et al, 2007). Level of work autonomy is found to have a strong influence on the employees' commitment (Culpepper, Gamble, & Blubaugh, 2004;Eby et al, 1999;Flynn & Tannenbaum, 1993;Malhotra et al, 2007;Mottaz, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has found that role clarity has an important role in employees' commitment towards their organizations (Bożena Bednarek-Michalska, 2002;Chi Ming Chow & Brian H. Kleiner, 2002;Manning et al, 2012;Parasuraman et al, 1990;Probst, 2003;Saks et al, 2007). Level of work autonomy is found to have a strong influence on the employees' commitment (Culpepper, Gamble, & Blubaugh, 2004;Eby et al, 1999;Flynn & Tannenbaum, 1993;Malhotra et al, 2007;Mottaz, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…La majorité des études ont analysé la contribution d'un seul type de régime de rémunération, en particulier le régime de participation à la propriété. Par exemple, Culpepper et al (2004) rapportent que la valeur de la contribution de l'employeur au régime de participation à la propriété est liée à l'engagement de continuité. Dans une autre étude, Long (2000) montre que l'incidence des régimes de partage des béné-fices sur l'engagement est influencée par une distribution des primes basée sur le rendement individuel et par la diffusion d'information complète sur le régime.…”
Section: Revue De La Littératureunclassified
“…Dans une autre étude, Long (2000) montre que l'incidence des régimes de partage des béné-fices sur l'engagement est influencée par une distribution des primes basée sur le rendement individuel et par la diffusion d'information complète sur le régime. Dans l'ensemble, les recherches antérieures témoignent d'un effet positif des régimes de rémunération sur l'engagement (Bayo-Moriones et LarrazaKintana, 2009;Buchko, 1993;Coyle-Shapiro et al, 2002;Culpepper et al, 2004;Howard et Dougherty, 2004;Klein, 1987;Long, 2000). Toutefois, certaines incertitudes persistent, par exemple l'engagement affectif peut être influencé (Bayo-Moriones et Larraza-Kintana, 2009) ou non (Culpepper et al, 2004) par la valeur pécuniaire octroyée à l'employé par le régime.…”
Section: Revue De La Littératureunclassified
See 2 more Smart Citations